Ictal downbeat nystagmus in Ménière disease: A cross-sectional study. (27th October 2020) - Lee, Sun-Uk; Kim, Hyo-Jung; Choi, Jeong-Yoon; Kim, Ji-Soo
Abstract : Objective: To determine the mechanism of ictal downbeat nystagmus in Ménière disease (MD), we compared the head impulse gain of the vestibulo-ocular reflex (VOR) for each semicircular canal between patients with (n = 7) and without (n = 70) downbeat nystagmus during attacks of MD. Methods: We retrospectively analyzed the results of video-oculography, video head-impulse tests, and cervical vestibular-evoked myogenic potentials (VEMPs) in 77 patients with definite MD who were evaluated during an attack. Results: Pure or predominant downbeat nystagmus was observed in 7 patients (9%) with unilateral MD during the attacks. All 7 patients showed spontaneous downbeat nystagmus without visual fixation with a slow phase velocity ranging from 1.5 to 11.2°/s (median 5.4, interquartile range 3.7–8.5). All showed a transient decrease of the head impulse VOR gains for the posterior canals (PCs) in both ears (n = 4) or in the affected ear (n = 3). Cervical VEMPs were decreased in the affected (n = 2) or both ears (n = 2) when evaluated during the attacks. Downbeat nystagmus disappeared along with normalization of the VOR gains for PCs after the attacks in all patients. During the attacks, the head impulse VOR gains for the PC on the affected side were lower in the patients with ictal downbeat nystagmus than in those without (Mann-Whitney U test, p < 0.001), while the gains for other semicircular canals did not differ between the groups. Conclusion: Downbeat nystagmus may be observed during attacks of MD due to an asymmetry in the vertical VOR or saccular dysfunction. MD should be considered in recurrent audiovestibulopathy and ictal downbeat nystagmus.